Performance of EPMp broiler duck fed various levels of lysine during starter period - M, Purba; T, Haryati; AP, Sinurat (Indonesian Animal Sciences Society, 2015)
The aim of this study was to determine optimal requirement of lysine of broiler EPMp ducks during starter period. The study was designed in a completely randomized design (CRD) with four dietary treatments, four replications, and each replication consisted of 10 ducks. The treatments were: T1 (ration, with 0.70% digestible lysine); T2 (ration, with 0.85% digestible lysine); T3 (ration, with 1.00% digestible lysine); T4 (ration, with 1.15% digestible lysine). Variables measured were: feed intake, body weight gain and feed conversion ratio (FCR). Results showed that average body weight gain of EPMp broiler ducks was significantly affected (P<0.05) by the level of lysine in the diet, but feed intake and FCR were not significantly (P>0.05) affected. Mean body weight gain of EPMp broiler duck with T4 ration (1.15%) of lysine was significantly higher compared to T3 ration (1.00% of lysine), but between T4 to T1 and T2 treatmeants were not significantly different (P>0.05). T3 treatment compared to T1 and T2 treatments were not significantly different (P>0.05). There is a pattern of decreasing feed consumption and FCR by increasing content of lysine in the diet, protein and lysine consumption during the starter period. It is concluded that administration of digested lysine at 0.70 and 0.85%, protein and metabolized energy respectively by 18% and 2800 kcal/kg EM in feed were considered sufficient to generate performance (feed consumption, body weight gain and FCR) of EPMp broiler ducks in starter period. Key Words: Performance, EPMp Ducks, Lysine, Starter